2008
DOI: 10.1159/000165349
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome and Migraine Headache, Is There Any Correlation?

Abstract: Background: To evaluate the role of some sex hormones in migraine headaches, the aim of this study was to assess the prevalence and characteristics of headache, especially migraine, in patients with polycystic ovary syndrome (PCO) compared with women without this disease. Methods: One hundred and thirty-three women with PCO and 107 controls were interviewed by 2 neurologists experienced in headache diagnosis. The headache disorders were classified according to the International Headache Society criteria. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In our study, women with PCOS ex pe ri enced head ache more fre quently than con trol women: 68.4% vs. 50.0%, p=0.010. We found only one study re lated to head ache in women with PCOS that showed lower rates of head ache in PCOS and con trols com pared with our re sults, re spectively 44.9% in women with PCOS and 33.8% in con trols [10]. Pourabolghasem et al also found no sig nif i cant differ ence of head ache fre quency be tween women with PCOS and con trols (OR=0.78, CI: 0.6-1.03, p=0.81) [10].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, women with PCOS ex pe ri enced head ache more fre quently than con trol women: 68.4% vs. 50.0%, p=0.010. We found only one study re lated to head ache in women with PCOS that showed lower rates of head ache in PCOS and con trols com pared with our re sults, re spectively 44.9% in women with PCOS and 33.8% in con trols [10]. Pourabolghasem et al also found no sig nif i cant differ ence of head ache fre quency be tween women with PCOS and con trols (OR=0.78, CI: 0.6-1.03, p=0.81) [10].…”
Section: Discussionsupporting
confidence: 81%
“…We found only one study re lated to head ache in women with PCOS that showed lower rates of head ache in PCOS and con trols com pared with our re sults, re spectively 44.9% in women with PCOS and 33.8% in con trols [10]. Pourabolghasem et al also found no sig nif i cant differ ence of head ache fre quency be tween women with PCOS and con trols (OR=0.78, CI: 0.6-1.03, p=0.81) [10]. Our re sults showed the op po site: PCOS in creased the odds ra tio for head ache by 2.17 (CI: 1.20-3.91, p=0.010).…”
Section: Discussionsupporting
confidence: 81%
“…Only patients with normal MRI findings (established by a neuroradiologist with 10+ years of experience) and no diagnosis of a disease associated with affliction of the endocrine axis were included. 14,15 According to these criteria, we could include a total of 144 patients. The most common indication for the MRI examination was headache.…”
Section: Methodsmentioning
confidence: 99%
“…Especially in women, oestrogen fluctuations are identified as a risk factor of migraine and migraine attacks [56]. Pourabolghasem et al suggested that there is no evidence that higher levels of male sex hormones (mainly testosterone) in female migraineurs with polycystic ovary syndrome (PCOS) intensify migraine attacks [59]. Glintborg et al reported that migraine was more prevalent in PCOS females [60].…”
Section: Discussionmentioning
confidence: 99%